2018
DOI: 10.3389/fimmu.2018.00926
|View full text |Cite
|
Sign up to set email alerts
|

MICA-129 Dimorphism and Soluble MICA Are Associated With the Progression of Multiple Myeloma

Abstract: Natural killer (NK) cells are immune innate effectors playing a pivotal role in the immunosurveillance of multiple myeloma (MM) since they are able to directly recognize and kill MM cells. In this regard, among activating receptors expressed by NK cells, NKG2D represents an important receptor for the recognition of MM cells, being its ligands expressed by tumor cells, and being able to trigger NK cell cytotoxicity. The MHC class I-related molecule A (MICA) is one of the NKG2D ligands; it is encoded by highly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…Here we showed that a high level of soluble sMICA, an NKG2D ligand, in sera of HCC patients was associated with poor outcome. Wan and his team [35] reported that MICA is released into circulation due to shedding of MICA from cell membranes during tumor transformation or upon stress. We showed that sMICA binds to cells expressing the NKG2D receptor but does not activate NKG2D receptor-mediated signaling and does not activate of NK cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Here we showed that a high level of soluble sMICA, an NKG2D ligand, in sera of HCC patients was associated with poor outcome. Wan and his team [35] reported that MICA is released into circulation due to shedding of MICA from cell membranes during tumor transformation or upon stress. We showed that sMICA binds to cells expressing the NKG2D receptor but does not activate NKG2D receptor-mediated signaling and does not activate of NK cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Met/Val (rs 1051792) polymorphism effect has been largely investigated for their role in infections, autoimmune diseases and cancer, including breast cancer and multiple myeloma (Boukouaci et al, 2009;Campillo et al, 2015;Douik et al, 2009;Isernhagen et al, 2015;Ouni et al, 2017;Raache et al, 2012;Zingoni et al, 2018). These data highlighted the important role played by this polymorphism in tumour escape from the immune system and consequently on breast cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…However, suppressive functions of TGF-β could be exerted also when the cytokine is not released in its soluble form but associated to exosomes, nanometer-sized vesicles actively secreted by different cell types, including tumor cells. Cancer cell-derived exosomes expressing TGF-β can downregulate NKG2D expression on NK and CD8+ T cells, while other receptors, including CD4, CD8, CD56, CD16, CD69, and CD94 are not affected, indicating the selectivity of the effect [44][45][46][47].…”
Section: Regulation Of Nk Cell Activating Signals By Tgf-βmentioning
confidence: 99%